The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11431-011-4609-4
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic generation of ruled surface based on rational motion of point-line

Abstract: This paper studies representation of rigid combination of a directed line and a reference point on it (here referred to as a "point-line") using dual quaternions. The geometric problem of rational ruled surface design is viewed as the kinematic problem of rational point-line motion design. By using the screw theory in kinematics, mappings from the spaces of lines and point-lines in Euclidean three-dimensional space into the hyperplanes in dual quaternion space are constructed, respectively. The problem of rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The RTS/CTS handshake protocol is an optional scheme on top of the Carrier Sense Multiple Access with Collision Avoidance (CSMA/CA) protocol [14] for a four-way handshake mode (RTS-CTS-DATA-ACK) [15]. It is proposed to solve the hidden terminal [11] problem, which refers to a node that is outside the coverage of the sending node but in the coverage of the receiving node, as illustrated in Figure 1.…”
Section: Overview Of the Rts/cts Handshake Protocolmentioning
confidence: 99%
“…The RTS/CTS handshake protocol is an optional scheme on top of the Carrier Sense Multiple Access with Collision Avoidance (CSMA/CA) protocol [14] for a four-way handshake mode (RTS-CTS-DATA-ACK) [15]. It is proposed to solve the hidden terminal [11] problem, which refers to a node that is outside the coverage of the sending node but in the coverage of the receiving node, as illustrated in Figure 1.…”
Section: Overview Of the Rts/cts Handshake Protocolmentioning
confidence: 99%
“…Pottmann et al explored offsets of rational ruled surfaces [12]. Furthermore, the geometry of ruled surfaces plays a crucial role in the study of kinematic and positional mechanisms, as demonstrated by Kühnel, Abdel Baky, Ekici and Çöken, Zhang, Ünlütürk et al and Ekici et al [13,14,15,16,17,18]. Similar to the fundamental theorem of curves, which facilitates the determination of a curve based on curvature and torsion, a similar structure can be recognized in the field of reconstruction of a ruled surface.…”
Section: Introductionmentioning
confidence: 99%
“…The wasp Pachyneuron aphidis Bouché (Hymenoptera: Pteromalidae) is a common hyperparasitoid of A. gifuensis and is the dominant hyperparasitoid of A. gifuensis in Yunnan province in China (Wei et al, 2003), where hyperparasitism reached 65% in tobacco (Chai, Kuang, & Zhu, 2013). Detailed investigations have been carried out on this hyperparasitoid's biology (Chai, Deng, & Wu, 2005;Chai, Kuang, & Zhu, 2008;Ming, Gu, Wei, & Zhang, 2005;Zhao, Zhu, Wu, & Gao, 2009), population dynamics (Chai et al, 2013) and olfactory responses (Zhang et al, 2012). The phototactic behaviour of the host aphid (Fu et al 2009) and the primary parasitoid (Chen, Kuang, Zhou, & Liu, 2012) have previously been examined but the phototactic behaviour of the hyperparasitoid P. aphidis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%